Deregulated Profiles of Urinary Micrornas May Explain Podocyte Injury and Proximal Tubule Dysfunction in Normoalbuminuric Patients with Type 2 Diabetes Mellitus. (April 2018) - Milas, Oana; Gadalean, Florica; Vlad, Adrian; Dumitrascu, Victor; Gluhovschi, Cristina; Gluhovschi, Gheorghe; Velciov, Silvia; Popescu, Roxana; Bob, Flaviu; Matusz, Petru; Pusztai, Agneta-Maria; Cretu, Octavian M; et al.
MicroRNAs (miRNAs) are short non-coding RNA species that are important post-transcriptional regulators of gene expression. The aim of the study was to establish a potential explanation of podocyte damage and proximal tubule (PT) dysfunction induced by deregulated miRNAs expression in the course of type 2 diabetes mellitus (DM). A total of 68 patients with type 2 DM and 11 healthy subjects were enrolled in a cross-sectional study and assessed concerning urinary albumin:creatinine ratio (UACR), urinary N -acetyl-β-D-glucosamininidase (NAG), urinary kidney injury molecule-1, urinary nephrin, podocalyxin, synaptopodin, estimated glomerular filtration rate (eGFR), urinary miRNA21, miRNA124, and miRNA192. In univariable regression analysis, miRNA21, miRNA124, and miRNA192 correlated with urinary nephrin, synaptopodin, podocalyxin, NAG, KIM-1, UACR, and eGFR. Multivariable regression analysis yielded models in which miRNA192 correlated with synaptopodin, uNAG, and eGFR (R 2 =0.902; P<0.0001), miRNA124 correlated with synaptopodin, uNAG, UACR, and eGFR (R 2 =0.881; P<0.0001), whereas miRNA21 correlated with podocalyxin, uNAG, UACR, and eGFR (R 2 =0.882; P<0.0001). Urinary miRNA192 expression was downregulated, while urinary miRNA21 and miRNA124 expressions were upregulated. In patients with type 2 DM, there is an association between podocyte injury and PT dysfunction, and miRNA excretion, even in the normoalbuminuria stage. This observation documents a potential role of the urinary profiles of miRNA21, miRNA124, and miRNA192 in early DN. Despite their variability across the segments of the nephron, urinary miRNAs may be considered as a reliable tool for the identification of novel biomarkers in order to characterize the genetic pattern of podocyte damage and PT dysfunction in early DN of type 2 DM.